Trimetazidine Attenuates Exhaustive Exercise-Induced Myocardial Injury in Rats via Regulation of the Nrf2/NF-κB Signaling Pathway - Zhang, Hongming; Liu, Moyan; Zhang, Yuyan; Li, Xiaoyan (Frontiers in Pharmacology, 2019)
Exhausted exercise has been reported to cause the damage of myocardial structure and function in terms of cardiomyocyte apoptosis, oxidative stress, and energy metabolism disturbance. Trimetazidine (TMZ), as an anti-ischemic agent, has been approved to be effective in promoting myocardial energy metabolism, anti-inflammatory, and anti-oxidation. However, few studies examined the effects of TMZ on myocardial injury induced by exhausted exercise. To investigate whether TMZ could ameliorate the exhaustive exercise-induced myocardial injury and explore the underlying mechanisms, here the rat model of exhaustive exercise was induced by prolonged swimming exercise and TMZ was administrated to rats before exhaustive exercise. According to the results, we demonstrated that exhaustive exercise led to cardiomyocyte damage in rats as evidenced by elevations in cTnI and NT-proBNP levels, and decrease in CX43 expression, which was attenuated by TMZ treatment. Moreover, the administration of TMZ was found to restrain exhaustive exercise-induced oxidative stress damage by increasing GSH level, SOD and GSH-Px activities, and decreasing MDA level. Additionally, TMZ ameliorated myocardial injury by inhibiting apoptosis via reducing Bax/Bcl-2 ratio and down-regulating cleaved caspase-3, cleaved PARP, and cytochrome c levels in the myocardium of rats. Furthermore, we found that TMZ suppressed oxidative stress and cardiomyocyte apoptosis via activation of Nrf2/HO-1 and inactivation of NF-κB signaling pathways. Therefore, our study suggested that TMZ provided cardioprotection in rats after exhaustive exercise, indicating TMZ might served as a potential therapeutic drug for exhaustive exercise-induced myocardial injury.